Evaluación financiera a la “Cooperativa de Ahorro y Crédito Loja Internacional Ltda”, de la ciudad de Loja, periodo 2014-2015 - Gòmez Piedra, Pamela Stefania (2016)
This thesis entitled FINANCIAL ASSESSMENT TO "credit union LTDA LOJA INTERNATIONAL" CITY OF LOJA, 2014-2015., Was made to meet the prerequisite to choose the title and Engineering Degree in Accounting and CPA audit of the National University of Loja. In the same general objective was raised to conduct a financial assessment to the "credit union LOJA INTERNATIONAL LTDA" 2014- 2015 period, application specific objectives PEARLS monitoring system were raised to evaluate the financial performance of operations Cooperative, the implementation of CAMEL method for corporate risk measurements and produce a final progress report with the results. The scientific research methods used in relation to the methodology used, and proceeded in the first instance to make the recognition of the entity under study to find the reference point for the formulation of the Financial Evaluation through interviews with the manager and Accountant, who provided the information necessary to determine the current situation facing the Cooperative. To start the process of financial evaluation proceeded to the review of the financial statements through the application of Financial Indices PEARLS system, the same that allowed a comprehensive analysis of its financial condition in terms of Protection, Financial Structure, Performance and 6 costs, Liquidity, nonperforming assets and Expansive Signs of the institution. The financial assessment process continues proceeding with the implementation of Financial Indices CAMEL Method through management or management using administrative efficiency indicators, financial efficiency and production efficiency. The results obtained in this thesis is determined by measuring the level of protection with indicator P6; the creditworthiness of the Cooperative for savings and contributions of partners in the case of liquidation of assets and liabilities, presents percentages of 99% in 2014 and 86% in 2015, ie that can cover almost all obligations with the public and the contributions of its partners, but nevertheless in a surprise liquidation may not meet such requirements, since the higher value of the assets is represented in the loan portfolio, amounts that are recoverable form periodic; while through yields and costs as this indicator has a goal of 100%; applying the R1 indicator the target set by this is from 15.76% to obtain as a result 23% by 2014 and 13% for 2015 allows for a difference of 10 points between each year this is because in 2014 with information collected was determined that are values that has been dragging from previous years on the contrary in 2015 it is recommended to managers of the cooperative improve and implement new policies collection to recover . In addition